The effect of the method of application of growth regulators on fruit quality of 'Einset seedless' grape (Vitis sp. L.) - Magdalena Kapłan (Acta Agrobotanica, 2012)
This study was conducted during the period 2006-2008 in the Faliszowice Vineyard in the Sandomierz Upland. The experiment evaluated yield quality of 'Einset Seedless' grape after the application of gibberellic acid (GA3) in the form of the growth regulator Arbostim 100 SL and 2-naphthoxyacetic acid (NOA) in the form of the growth regulator Betokson Super 050 SL. These growth regulators were applied during flowering by spraying the inflorescences or immersing them in whole at the following concentrations: 100 mg×L-1 GA3 - the treatment was performed once at full flowering (70-80% of open flowers); 50 mg×L-1 GA3 - the treatment was performed twice: at the beginning of flowering (20% of open flowers), and the second time at the end of flowering (80% of faded flowers); 50 mg×L-1 GA3 + 0.2% NOA - the treatment was performed once at full flowering; and 0.2% NOA - the treatment was performed once at full flowering. The study showed that the applied treatments had a beneficial effect on cluster and berry weight as well as on the number of berries per cluster in the grape variety 'Einset Seedless'. Gibberellic acid and the mixture of 50 mg×L-1 GA3 and 0.2% NOA were shown to have a significant effect on cluster and berry length; an exception were clusters and berries sprayed with 50 mg×L-1 GA3 whose length did not differ significantly compared to the control ones. The applied treatments slightly affected berry width in the grape variety under study. The growth regulators applied were found to have an adverse effect on extract content in 'Einset Seedless' fruit.